Techno-economic feasibility and size optimisation of an off-grid hybrid system for supplying electricity and thermal loads. (15th January 2021) - Das, Barun K.; Tushar, Mohammad Shahed H.K.; Zaman, Forhad
Abstract: In this article, cost-effective hybrid solutions while meeting the electric and thermal loads in five different climate zones in Australia are investigated. This study considers the excess electricity (EE, via thermal load controller-TLC) utilisation for the first time combined with recovered waste heat to satisfy the thermal load demand while the system is optimised using HOMER software. The micro gas turbine (MGT), diesel generator (DG), and fuel cell (FC), used as supplemental prime movers, along with the PV/Wind/Li-ion, are compared. This article also compares the hybrid energy system (HES) with power only and using EE and recovered waste heat individually and a combination of both to satisfy the thermal demand. Results indicate that the PV/Wind/MGT/Li-ion-based hybrid options have a lower Cost of Energy (COE, /kWh) in all areas with the lowest in Tasmania (0.140/kWh). Additionally, Queensland has higher COE (0.178/kWh) for the same hybrid options because of the lower solar irradiation and wind velocity. The FC-based hybrid options have higher COE and net present cost (NPC) compared to the DG- and MGT-based options. Utilising both EE and recovered waste heat for supplying thermal demand could lead to lower the components capacity – thus lowering the NPC and reducing the environmental emissions. Highlights: Five different climatic zones in Australia have been studied. Excess electricity and waste heat recovery options are used for thermal loads. Diesel generator, micro gas turbine, and fuel cell are used for PV/Wind hybridisation. Components sizes are significantly reduced using excess electricity and waste heat. Substantial net present cost (∼20%) and CO2 emissions (16%) have been reduced.